Novel Naproxen Salts with Increased Skin Permeability - Ewelina Świątek; Paula Ossowicz-Rupniewska; Ewa Janus; Anna Nowak; Peter Sobolewski; Wiktoria Duchnik; Łukasz Kucharski; Adam Klimowicz (MDPI AG, 2021)
The paper presents the synthesis, full identification, and characterization of new salts-L-proline alkyl ester naproxenates [ProOR][NAP], where R was a chain from ethyl to butyl (including isopropyl). All obtained compounds were characterized by Nuclear Magnetic Resonance (NMR), Fourier transform infrared spectroscopy (FTIR), X-ray powder diffractometry (XRD), and in vitro dissolution studies. The specific rotation, phase transition temperatures (melting point), and thermal stability were also determined. In addition, their lipophilicity, permeability, and accumulation in pigskin were determined. Finally, toxicity against mouse L929 fibroblast cells was tested. The obtained naproxen derivatives showed improved solubility and higher absorption of drug molecules by biological membranes. Their lipophilicity was lower and increased with the increase in the alkyl chain of the ester. The derivative with isopropyl ester had the best permeability through pigskin. The use of L-proline isopropyl ester naproxenate increased the permeation of naproxen through the skin almost four-fold. It was also shown that the increase in permeability is not associated with additional risk: all compounds had a similar effect on cell viability as the parent naproxen.